Antithrombotic potential of Berberis calliobotrys extract - Alamgeer, .; Asif, Hira; Rasool, Shahid (Bangladesh Journal of Pharmacology, 2016)
This study was focused with the aim to investigate the antithrombotic potential of Berberis calliobotrys. Aqueous-methanolic extract and various fractions showed significant (p<0.05-0.001) increase in prothrombin, activated partial thromboplastin and clotting time while only aqueous methanolic extract caused clot lysis when added to the blood samples of rabbit and human. In vivo study in rabbits, butanolic fraction (100 mg/kg) produced more significant prolongation in bleeding, prothrombin, activated partial thromboplastin and clotting time. Interestingly butanolic fraction had shown more pronounced effects among all tested extracts both in vivo and in vitro studies. Hence, it was subjected to antilipid peroxidation and phytochemical studies (total falvonoid contents, HPLC-DAD profile, FTIR). In conclusion, B. calliobotrys induce transient changes in the coagulation parameters, may it possess active constituents responsible for its antithrombotic potential. Video Clips of Methodology: Clotting time: 1 min 8 sec Full Screen Alternative Prothrombin time: 2 min 43 sec Full Screen Alternative